Self-assessment: A learner-centred approach towards transforming traditional practices and building self-directed learners - Sosibo, Z.C. (South African Journal of Higher Education, 2019)
During this learner-centred teaching and learning era, self-assessments may be a viable tool to enable university students to become autonomous and self-directed learners. Sadly, students rarely obtain self-assessment opportunities. This action research investigated student teachers’ self-assessment experiences, in order to establish how self-assessments contributed to self-directed learning. The research question was ‘What are students’ experiences of self-assessments’? Answers about SDL were embedded in students’ responses. Qualitative data were collected through interviews and quantitative data were obtained from students’ self-assessment and lecturer’s scores. Qualitative data analysis was done through coding and emergent themes, whereas quantitative data were analysed statistically and presented in descriptive statistics, bar graphs and scatterplots. Andragogy and constructivism informed this study. Although qualitative results revealed that students had attained some SDL skills, quantitative results showed that the students were still far from attaining these skills, as indicated by low correlations and a wide range between students’ and lecture’s scores. The researcher recommended that lecturers increase self-assessment opportunities for students; integrate self-assessments across different courses and adopt student-centred assessment approaches.